Gene expression induced by abiotic stress in cowpea nodules - Silva, Helder Anderson Pinto da; Galisa, Péricles de Souza; Oliveira, Roselaine Sanches da Silva; Vidal, Marcia Soares; Simões-Araújo, Jean Luiz (Pesquisa Agropecuaria Brasileira, 2012)
<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The objective of this work was to evaluate the isolated or concomitant effect of drought and heat stresses on the gene expression of cowpea nodules. The bacterium Bradyrhizobium japonicum (strain BR 3267) was inoculated in cowpea seeds from the cultivar IPA 206 and, 35 days after germination, the plants were subjected to different water availability regimes and to heat stress under greenhouse conditions. To identify differentially expressed genes, the cDNA‑AFLP technique was used, and 67 differentially expressed transcript‑derived fragments (TDFs) were isolated. After TDFs sequencing and similarity analyses, using the Blastx program, 14 differentially expressed genes were identified, which are involved in different metabolic processes. The expression pattern of six genes under abiotic stress conditions was confirmed by RT‑qPCR, and the induction of different functional gene categories, such as abscisic acid biosynthesis, cell signaling, proline transporter, and lipid membrane biosynthesis, was observed. The expression of these genes indicates their participation in processes related to nodule protection under abiotic stresses.